The ‘Cage Climber’: a new enrichment for use in large-dimensioned mouse facilities - Vogt, Miriam A.; Mertens, Sinja; Serba, Susanne; Palme, Rupert; Chourbaji, Sabine (Applied animal behaviour science, 2020)
Environmental Enrichment has been shown in experimental contexts to have clear and often beneficial effects on animal physiology and behavior. Housing prior to experiments can represent a large proportion of an animal’s living conditions, and improving housing conditions can be seen as “refinement” in a 3R-Context. However, large-dimensional implementation in rodent facilities often lack systematic analysis of respective refinement measures. Although enrichment is a legally binding element for housing animals according to EU law, potential effects on data variability are often neglected or not taken in consideration for experimental designs. Here, we aimed at implementing a new and innovative tool to improve wellbeing without side effects applicable for male and female mice. This poses a great challenge since the social structure in this species allows group housing in females without the risk of aggressive interaction, while in males despotic dominance hierarchy is often associated with agonistic interactions. Thus, we focused on enrichment-induced changes in behavior and stress physiology emphasizing effects on data variability in both sexes. Accordingly, recycled cage lids (resembling sex-neutral early environmental experiences in mice) were formed and three shapes of different structures were examined (‘Cage Climber’): ‘Triangle Climber’, ‘Bridge Climber’ and ‘Round Arch Climber’. The results demonstrate significant preferences of C57BL/6 N mice for any of the three structures in comparison with a neutral object when presented in a Novel Object Test. Despite intense use of enrichment, there were neither behavioral alterations detectable in a test battery assessing locomotion, anxiety and sociability nor in assessment of stress physiological parameters such as stress hormone metabolites, analyzed non-invasively from feces. Additionally, the structural supplement did not affect general variability of data in both male and female mice. To promote well-being of mice in a 3R-matched context, our study recommends the use of properly assessed structural enrichment, such as ‘Cage Climbers’ combined with nesting material to satisfy physical and thermal needs in the cage environment.
Gesehen am 14.10.2020